The Effective Factors on Continuity of Corporate Information Security Management: Based on TOE Framework - Yongho Kim (MDPI AG, 2021)
In the Fourth Industrial Revolution era, data-based business management activities among enterprises proliferated are mainly based on digital transformation. In this change, the information security system and its operation are emphasized as essential business activities of enterprises the research aims to verify the relationship among the influence factors of corporate information security management based on the TOE framework. This study analyzes the effects of technical, organizational, and environmental factors on the intention, strengthening, and continuity of information security management. To this, a survey was conducted on professional individuals who are working in areas related to information security in organizations, and 107 questionnaires were collected and analyzed. According to major results of the analysis on adopted hypotheses. In results, as to the intention of information security management, organization and environment factors were influential. In the other side, technology and environment factors were affected to the strengthening of information security management. Hence this study pointed out that the environmental factors are most significant for the information security administration of an organization. In addition, it turned out that the strengthening of information security management was influential on the continuity of information security management more significantly than the intention of information security management.